Iacta Alea Est: The Inexorable Advance of Tofacitinib in the Treatment of Dermatomyositis-Associated Rapidly Progressive Interstitial Lung Disease. A Case Report - Conca, Walter; Weheba, Ihab; Abouzied, Mohei-Eldin; Abdelsayed, Abeer; Aleyouni, Yousif; Al‐Mutairy, Eid; Bakshi, Nasir; Khalid, Mohammad (Frontiers in Pharmacology, 2020)
Rapidly progressive (RP) interstitial lung disease (ILD) is typically associated with clinically amyopathic (CA) dermatomyositis (DM) and the anti-melanoma differentiation associated gene 5 (MDA5) antibody, a condition with high mortality and resistance to classic immunosuppression. Recent reports have described the efficacy of the Janus kinase (JAK) inhibitor tofacitinib in the treatment of RPILD in anti-MDA5 antibody-positive CADM. It is uncertain, however, whether tofacitinib alters the course of RPILD in other variants of DM that are unrelated to the anti-MDA5 antibody and whether the early addition of the anti-fibrotic tyrosine kinase inhibitor nintedanib interferes with the development of fibrosis. To answer these questions, we present and discuss the case of an elderly woman who presented with a flare of DM sine myositis. Based upon the detection of anti-Jo-1 antibodies and the absence of anti-MDA5 antibodies, anti-synthetase syndrome (ASS) was diagnosed. While the cutaneous manifestations quickly resolved with prednisone, azathioprine and tacrolimus, the respiratory function paradoxically and rapidly deteriorated, and invoked the use of tofacitinib. Markedly raised ferritin levels and a severe numerical deficiency of circulating natural killer (NK) cells paralleled the acute lung inflammation, which was reflected by 18F-fluorodeoxyglucose (FDG) hypermetabolism on positron emission tomography (PET)/CT. Tofacitinib lead to a prompt clinical recovery, with a reduction in oxygen requirement, correction of hyperferritinemia, reversal of the NK cell deficiency, and a decrease in 18F-FDG uptake in the affected lung segments. Subsequently, nintedanib was added at a point in time when inflammation subsided. Apart from cytomegalovirus reactivation no adverse events occurred. In conclusion, tofacitinib reversed the pronounced inflammatory component of anti-Jo-1 antibody-positive, anti-MDA5 antibody-negative RPILD, confirming that JAK signaling pathways are critically involved in the pathogenesis of RPILD, apparently independently of the targeted autoantigen. Although some improvement in pulmonary function was observed, it seems premature to conclusively judge on reversibility or prevention of pulmonary fibrosis by pairing both kinase inhibitors for which an extended follow-up and ideally, prospective and controlled studies are needed.